The mollusc as a suitable model for mammalian immune-neuroendocrine - E Ottaviani (Invertebrate Survival Journal, 2004)
The same or relatively similar molecules seen in molluscan defense responses are also found inmammals, where their functions remain basically similar. The mollusc immunocytes are able torecognize a variety of stimuli and to set up correspondingly complex responses, in which primitive, butvery efficient, forms of immune and neuroendocrine responses are intermixed. Thus, invertebratescould represent an ideal alternative in studying mammalian complexity from an immunoneuroendocrinepoint of view.